The Effect of Loving Pregnancy Massage on Sleep Quality of Trimester III Pregnant Mother - Sri Wahyuni Rahayu; Sinar Pertiwi; Etin Rohmatin (Poltekkes Kemenkes Semarang, 2020)
Background: Third trimester of pregnancy was the peak of discomfort that was often experienced by pregnant women due to physical changes and psychological changes, which cause the mother's sleep was not quality. Treatment of sleep disorders can be overcome by pharmacological and non-pharmacological ways. Loving pregnancy massage provides a relaxing effect that can help solve discomfort problems, especially those related to sleep disorders..Methods: This study used a pre-experimental method with one group pretest-posttest design. The population of this study were pregnant women in their third trimester in Purbaratu Health Center, Tasikmalaya City. A sample of 31 people was taken by purposive sampling. The dependent variable was the sleep quality of the third trimester of pregnant women and the independent variable is loving pregnancy massage. The research instrument used The Pittsburgh Sleep Quality Index (PSQI) questionnaire with Wilcoxon test data analysis.Results: The results showed that the sleep quality of pregnant women before doing massage was in the moderate sleep disorder category (64.5%) and after the massage there was a decrease in the quality of sleep into a good category (54.8%). The Wilcoxon test results obtained a significance value of 0.000.Conclusion: there was a relationship between loving pregnancy massage and the sleep quality of third trimester pregnant women.